Personality traits in Southeast Asia: Evidence from rural Thailand and Vietnam - Dorothee Buehler; Rasadhika Sharma; Wiebke Stein (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2019)
The aim of this paper is twofold: First, we implement and validate the famous Big Five model on personality traits in a rural developing country setting. Second, we provide micro level evidence that examines personality traits of rural households in Thailand and Vietnam. Using new representative individual level data, our results show that the Big Five model can be applied in a rural setting. Moreover, we find substantial differences in personality traits between the rural populations of Thailand and Vietnam as well as persistent gender differences among both emerging societies.
Keywords: D91; O1; R2; 330; Personality traits; Big Five Factor Model; Southeast Asia; TVSEP